A comparative study of graphene oxide affecting the nanoarchitecture and electrochemical properties of urchin-shape nickel cobalt oxide. (March 2017) - Zhifu, Feng; Haihong, Wu; Zhikun, Li; Baocheng, Yang; Nielsen, Peer; Weiyang, Zhang
Abstract: The study of graphene oxide (GO) influencing on nanoarchitecture and chemical properties of the urchin-shape NiCo2 O4 has been detected. The urchin nanostructure of NiCo2 O4 was easily destroyed by GO, and the nanorods of NiCo2 O4 no longer reunite to urchin shape. Specifically, when there was 0.096g GO fixed with NiCo2 O4 (NiCo-4GO), the specific surface area enlarged by 530%, and the specific surface area of mespores increased by 588% compared to pure NiCo2 O4 (NiCo-0GO). Besides, electrochemical properties also experienced enormous change. The specific capacitance of NiCo-4GO decreased from 1580 F g -1 of NiCo-0GO to 880 F g -1 at 1 A g -1 . The resistance of composites raised gradually with increasing the dosage of GO. Furthermore, products possessed an enhancive cycling stability. NiCo-4GO maintained 84% after 1000 CV cycles. The influence of Graphene nanosheets(GN) on NiCo2 O4 was also observed in contrasted with that of GO. Unexpectedly, the result of FT-IR and Raman spectras of samples revealed that certain bonds were truly affected and produced in the composite with GO and NiCo2 O4 .